Conduction slowing area during sinus rhythm harbors ventricular tachycardia isthmus. (20th January 2020) - Ueda, Akiko; Soejima, Kyoko; Nakahara, Shiro; Fukuda, Reiko; Fukamizu, Seiji; Kawamura, Iwanari; Miwa, Yosuke; Mohri, Takato; Katsume, Yumi; ,
Abstract: Introduction: The voltage map during sinus rhythm (SR) is a cornerstone of substrate mapping (SM) in scar‐related ventricular tachycardia (VT) and frequently used with pace mapping (PM). Where to conduct PM is unclear in cases of an extensive or unidentified substrate. Conduction properties are another aspect incorporated by SM, and conduction slowing has gained interest as being related to successful ablation, although its mechanism has not been elucidated. We aimed to investigate the relationship between SR conduction properties and VT isthmuses. Methods: Nineteen patients (mean age, 62 years) who underwent VT ablation with voltage mapping and PM were reviewed. Isochronal late activation maps (ILAMs) with eight zones were reconstructed and sequentially named from one to eight according to the SR propagation. Good PM sites were superimposed on ILAMs, and the isthmus was defined using different pacing latencies. ILAM properties harboring isthmuses were investigated. Results: Twenty‐eight ILAMs (13 epicardium, 1 right ventricular [RV], and 14 left ventricular [LV] endocardium) were reviewed. Eighteen isthmuses of 24 target VTs were identified, in which the proximal ends were in a later zone than the distal ends (zone 6 vs 4; P < .001), suggesting a reverse isthmus vector to the SR. The conduction velocity of the zone involving the distal isthmus was significantly lower than that of the SR preceding zone (0.40 vs 1.30 m/s; P < .001). SR conduction velocity decelerated by 69.5% (range 59.7%‐74.5%) before propagating into the isthmus area. Conclusion: Conduction slowing area during SR were related with the exit portion of the VT isthmuses.